Depression and Anxiety in Patients with COPD: A Focus on Psychological Treatments in Ambulatory Care Settings - Mignogna, Joseph; A. Cully, Jeffrey (Current Respiratory Medicine Reviews, 2012)
Depression and anxiety are highly comorbid with chronic obstructive pulmonary disease (COPD) and are associated with poor treatment adherence, increased rates of physical disability, functional disability, mortality, healthcare costs, and a worsening quality of life. Despite its prevalence, there is a dearth of research on psychological treatments for depressed and/or anxious patients with COPD. This review examines the current evidence for psychological treatments for depression and anxiety in COPD, structured within the RE-AIM (Reach, Effectiveness, Adoption, Implementation and Maintenance) framework, in an effort to highlight the current practice and research needs for this important and complex patient population.
Keywords: Ambulatory care